Salicylic Acid Treatment Improves the Shelf Life and Quality of ‘Cheonghyang’ Grapes during Cold Storage - Zebro, Mewuleddeg; Heo, Jae-Yun (South African Journal of Enology and Viticulture, 2024)
The storage capacity of ‘Cheonghyang’ grapes, a promising grape cultivar developed in South Korea, is a critical factor affecting their commercial viability. This study investigates the impact of salicylic acid (SA) treatment on the storage capacity of ‘Cheonghyang’ grapes. The effects of SA treatment at different concentrations were assessed by comparing fruit characteristics and enzyme activity related to shelf life after two and four weeks of cold storage in comparison with an untreated control group. The findings reveal that SA-treated grapes exhibited reduced water loss and improved firmness, leading to a lower occurrence of unmarketable berries. Furthermore, enzymes involved in pectin degradation, such as pectate lyase and polygalacturonase, were reduced in the SA-treated group, while antioxidant activity-related enzymes, including catalase, peroxidase and superoxide dismutase, were more active than in the control group. The most effective control of enzyme activities was observed at an SA concentration of 2 mM, which demonstrated the least decline in fruit quality among the tested SA concentrations in this study. These results indicate that SA is a highly effective substance for maintaining the storability of ‘Cheonghyang’ grapes under conditions of low-temperature storage after harvest.